2010
DOI: 10.1038/nphys1686
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion generated by diffusion-driven flow

Abstract: Buoyancy-driven flow, which is flow driven by spatial variations in fluid density 1 , lies at the heart of a variety of physical processes, including mineral transport in rocks 2 , the melting of icebergs 3 and the migration of tectonic plates 4 . Here we show that buoyancy-driven flows can also generate propulsion. Specifically, we find that when a neutrally buoyant wedgeshaped object floats in a density-stratified fluid, the diffusiondriven flow at its sloping boundaries generated by molecular diffusion prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
(12 reference statements)
2
30
0
Order By: Relevance
“…3, a). The principal mechanism of the phenomena lies in the pressure deficiency which is sufficient for description of the observed displacement of a body under conditions of laboratory experiment [10]. The minimum pressure values are fixed on the impermeable wall of the wedge (Fig.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, a). The principal mechanism of the phenomena lies in the pressure deficiency which is sufficient for description of the observed displacement of a body under conditions of laboratory experiment [10]. The minimum pressure values are fixed on the impermeable wall of the wedge (Fig.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…The integral force action of convergent flows, absent in the symmetric obstacles (sphere, cylinder or horizontal plate), assumes a finite value on the inclined plate and other bodies, non-symmetrical with respect to the line of gravity. The resulting pressure gradients are large enough and capable of inducing self-motion of the neutral buoyancy free bodies («diffusion fish» in parlance of article [10,11]), which plays an important role in the dynamics of the hydrosphere. Calculation of steady flows on the flat fixed wedge is carried out in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite almost a century of research [6], although there have been a few studies of the motion of objects floating on the surface of [7], or immersed within [8], flows driven by natural convection, studies of boundary-induced natural convection have been restricted to systems with fixed boundaries [9]. Recently it has been demonstrated that a related class of boundary-layer flow, driven by molecular diffusion, can propel objects immersed in a fluid [10], albeit very slowly. Boundary-layer flows generated via natural convection are typically orders of magnitude stronger than their diffusive counterpart, and therefore have the potential to generate substantially faster propulsion speeds.…”
mentioning
confidence: 99%
“…This gives a full boundary thickness δπ = 16 mm. This should be resolvable with careful use of PIV, as it is about 50% the thickness of the well-resolved velocity field in Allshouse et al [2010].…”
Section: C Appendix -Studying the Effects Of Topography In The Labomentioning
confidence: 99%